Pressure sensing utilizing linear cavity erbium-doped fiber laser - Idris S.M.; Abdullah F.; Al-Mansoori M.H.; Jamaludin M.Z.; Din N.M. (2023)
In this paper, we report a fiber laser pressure sensor based on linear cavity erbium-doped fiber laser. The fiber laser structure comprises of an erbium-doped fiber amplifier, a circulator, an optical coupler and a fiber Bragg grating (FBG) which acts simultaneously as a lasing wavelength selecting components as well as a pressure sensor. The FBG is fitted to the shock tube where the pressure is applied. The fiber laser pressure sensor has a low threshold power of 7 mW, an output power of 2.28 mW and an optical signal to noise ratio over 55 dB. The proposed fiber laser sensor is expected to be an attractive choice for long-distance pressure monitoring. 2010 Pleiades Publishing, Ltd.